The Role of Extension Workers in Pepper Farming (Piper Nigrum) in Batu Timbau Village, Batu Ampar Sub-District, East Kutai District - Muhamad Yazid Bustomi; Nursida; Riski Adi Pratama; Pandhu Rochman Suosa Putra; Andi Lelanovita Sardianti (P2M Politeknik Pertanian Negeri Samarinda, 2023)
The development of pepper farming in Batu Timbau Village cannot be separated from the role of agricultural extension workers in encouraging and providing information to farmers. This study aimed to determine the role of extension workers in pepper farming in Batu Timbau Village, Batu Ampar Sub-District, which is seen from the aspects of motivators, educators, catalysts, organizers, and communicators. This research was carried out in 2021 in Batu Timbau Village, Batu Ampar Sub-District, East Kutai District. The sampling technique in this study used the census method with a total sample of 47 pepper farmers. The data analysis method used was descriptive statistics with a 3-item Likert scale. The results showed that the role of extension workers for pepper farmers in Batu Timbau Village was included in the role category seen from five aspects of the assessment. The role of extension workers for pepper farmers in the motivator aspect was included in the interval between 391.71 - 548.30 which is included in the role category with a value of 488. In the educational aspect, it is included in the interval of the role category with a value of 472. In addition, the aspect of organizers, communicators, and catalysts are in the interval of role categories with values of 485, 502, and 545 respectively.